Microbial Poly‐3‐Hydroxybutyrate (PHB) as a Feed Additive for Fishes and Piglets. Issue 12 (27th June 2019) - Wang, Xuan; Jiang, Xiao‐Ran; Wu, Fuqing; Ma, Yiming; Che, Xuemei; Chen, Xiyue; Liu, Ping; Zhang, Wenbing; Ma, Xi; Chen, Guo‐Qiang
Abstract : The large‐scale use of petrochemical‐based plastics is damaging our environment. Discarded plastics are harmful to both marine and land animals, sometimes causing death when ingested. Biodegradable plastics have gained attentions from the public and the academia to reduce environmental burdens. Poly‐3‐hydroxybutyrate (PHB), the simplest and the best‐studied bioplastic member of the polyhydroxyalkanoate (PHA) family synthesized by many bacteria, has been studied as a feed additive for large yellow croaker fish and weaned piglets. The fish grow faster and gain more weight when 1% and 2% PHB is added as a feed additive, accompanied by increased survival rates. Weaned piglets are found to grow normally and showed no significant change in average daily weight gains, average daily feed intakes, feed efficiency, and organ developments when 0.5% PHB is added to the feed. It can therefore be concluded that biodegradable and biocompatible PHB is not harmful as a feed additive for marine large yellow croakers and sensitive weaned piglets. PHB therefore holds great promise as a plastic that combines biodegradability and biocompatibility with good tolerability as a feed supplement for animals. Abstract : Poly‐3‐hydroxybutyrate is not harmful as a feed additive for marine large yellow croakers and sensitive weaned piglets. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visit www.afob.org .